Evaluation of Implementation of Maslow's Hierarchy of Needs to Fulfil the Needs of Freelance Journalist and Adaptation of Psychological Contract into Employment Relationship in Hong Kong - Vincent Hing-Po Lam (Randwick International of Social Science Journal, 2020)
The large news newspaper and media corporation previously provides long-term and stable career for journalist to move up on the career path from junior reporter to become editor in chief. Maslow's hierarchy of needs has been used as the motivation paradigm to fulfil every stage of needs from physiological needs to the highest form of self-actualization needs. However, when the change of media market employment relationship and social media as the main focus of news content, more large media corporation uses contracted freelance journalist with expertise in their particular field as as finance, politics, sports, horse racing, travel, dine and wine as content contributor. The relationship between news corporation and journalist has changed from employment to partnership. Therefore, it remains in doubt whether Maslow's hierarchy of needs still hold for staff management in today media industry.In addition, freelance journalist is himself a KOL and expert in their field and their follower helps the media platform increase the readership and click rate which translates into increasing their advertising revenue. As such, there is psychological contract which consists of intrinsic (Pay) and extrinsic values (other factors) and different expectation from both party on this employment contract in this new form of partnership.The aim of this paper is to examine from freelance journalists point of view whether Maslow's hierarchy of needs applies on them and what are the extrinsic values which hold them on this employment relationship with media corporation.